Evaluate the Association Between IL-37 Isoform-C and D Gene Expression with the Severity and Activity of Rheumatoid Arthritis - Furqan Hasan Razzaq; Rana Fadhil Obaid (مجلة الكوفة الطبية)
Background: Rheumatoid arthritis (RA) is a systemic, chronic autoimmune condition characterized by joint inflammation and pain, leading to the degeneration of the joints and bones, which may develop into deformities. The identification of the potential of new RA biomarkers, such as IL-37 isoforms for diagnosis and treatment applications is now under investigation. Purpose: This research aims to investigate the connection between the expression of IL37 isoform-c and IL37 isoform-d genes with RA activity and severity, their rules in diagnosis of the disease and for future RA therapeutic purposes. Methods: A case-control study was conducted on a total of 140 individuals. A total of 70 patients, who were recently diagnosed with rheumatoid arthritis by a rheumatologist, were included in the study, along with 70 control volunteers. The samples were obtained by using freshly acquired blood and serum samples via the use of RT-qPCR, ELISA, and other methods. The sample included 64 females and 6 men in both the patient and control groups. The age ranges from 20 to 70 years. Specimens were gathered between August 2023 and December 2023 from the Rheumatology department at AL-Sader Medical City in Najaf Governorate, Iraq. The blood IL-37 level was quantified using an enzyme-linked immunosorbent assay (ELISA). Additionally, immune markers including Anti-CCP, ESR, RF, and CRP were assessed. The quantification of IL-37 isoforms' gene expression was performed using qRT-PCR. The activity of rheumatoid arthritis (RA) was assessed using DAS28-ESR, DAS28-CRP, and CDAI, which also allowed for the determination of disease severity. Results: The levels of inflammatory parameters including Anti-CCP, CRP, RF, and ESR were significantly elevated in RA patients in compared to controls. IL-37 isoform-c mRNA expression, as determined by RT-qPCR, has significantly greater expression in the patients' group. It was upregulated in moderate groups of patients. Furthermore, the isoform-d gene was downregulated, in contrast to control groups for both genes, who exhibited normal expression for these genes. And there was a non-significant association between IL37 isoforms c and d expression and RA activity and severity. However, IL37-c expression increased within the moderate patient groups based on severity and activity categorization as compared to controls.    Conclusion: IL37 isoform-c and isoform-d are considered as a weak biomarker for diagnosing RA, evaluating disease activity and severity for RA patients.